Transformasi Wacana Pluralisme dalam Islam Pasca-9/11: Studi Komparatif antara Islam Barat dan Islam Nusantara - Muhammad Hidayatulloh; Zakaria Anshar; Ahmad Zakir Bin Hasan (Yayasan Albahriah Jamiah Indonesia, 2025)
The events of 9/11 triggered significant changes in the global construction of Islam and gave rise to an academic need to examine how Islamic pluralism is produced in different social contexts, especially since comparative studies that explicitly map the transformation of discourse between Western Islam and Islam Nusantara are still limited. This study aims to map the patterns of construction, negotiation, and reproduction of post-9/11 pluralism discourse in both contexts and analyze the epistemological, historical, and political factors that influence these shifts. Using qualitative methods through comparative discourse analysis based on a critical analysis framework, this study examines a corpus of academic texts, public policies, and popular discourse selected through the criteria of thematic relevance and representation of social context, thus enabling a systematic mapping of the emerging discourse categories. The results show measurably different patterns of transformation: Western Islam displays a discourse oriented towards issues of integration, security, representation of minority identities, and articulation of Islam’s compatibility with modern citizenship values, reflected through dominant themes such as narratives of coexistence, reformulation of Muslim-non-Muslim relations, and affirmation of the legality of the existence of Muslim communities in the public sphere. In contrast, Islam Nusantara produces a more dialogic and layered discourse through the articulation of values ​​of social harmony, local religious authority, historical memory of diversity, and stable cultural legitimacy, which are evident in discourse categories such as adat-sharia integration, communal harmony, and religious moderation. These findings confirm that post-9/11 Islamic pluralism developed differently according to local social structures, collective memories, and political dynamics, while contributing to broadening the perspective of contemporary Islamic studies and strengthening the approach to cross-cultural dialogue.